Muscle stimulation in advanced idiopathic pulmonary fibrosis: a randomised placebo-controlled feasibility study. Issue 6 (2nd June 2021) - Nolan, Claire M; Patel, Suhani; Barker, Ruth E; Walsh, Jessica A; Polgar, Oliver; Maddocks, Matthew; George, Peter M; Renzoni, Elisabetta A; Wells, Athol U; Molyneaux, Philip L; Kouranos, Vasilis; Chua, Felix; et al.
Abstract : Objectives: To assess the acceptability of neuromuscular electrical stimulation (NMES) of the quadriceps muscles in people with idiopathic pulmonary fibrosis (IPF) and to identify whether a future definitive trial is feasible. Design: A randomised, parallel, two-group, participant and assessor-blinded, placebo-controlled feasibility trial with embedded qualitative interviews. Setting: Outpatient department, Royal Brompton and Harefield Hospitals. Participants: Twenty-two people with IPF: median (25th, 75th centiles) age 76 (74, 82) years, forced vital capacity 62 (50, 75) % predicted, 6 min walk test distance 289 (149, 360) m. Interventions: Usual care (home-based exercise, weekly telephone support, breathlessness management leaflet) with either placebo or active NMES for 6 weeks, with follow-up at 6 and 12 weeks. Primary outcome measures: Feasibility of recruitment and retention, treatment uptake and adherence, outcome assessments, participant and outcome assessor blinding and adverse events related to interventions. Secondary outcome measures: Outcome measures with potential to be primary or secondary outcomes in a definitive clinical trial. In addition, purposively sampled participants were interviewed to capture their experiences and acceptability of the trial. Results: Out of 364 people screened, 23 were recruited: 11 were allocated to each group and one was withdrawn prior to randomisation. Compared with the control group, a greater proportion of the intervention group completed the intervention, remained in the trial blinded to group allocation and experienced intervention-related adverse events. Assessor blinding was maintained. The secondary outcome measures were feasible with most missing data associated with the accelerometer. Small participant numbers precluded identification of an outcome measure suitable for a definitive trial. Qualitative findings demonstrated that trial process and active NMES were acceptable but there were concerns about the credibility of placebo NMES. Conclusions: Primarily owing to recruitment difficulties, a definitive trial using the current protocol to evaluate NMES in people with IPF is not feasible. Trial registration number: NCT03499275 .